Phylogenetic analysis and structural prediction reveal the potential functional diversity between green algae SWEET transporters - Fleet, Jack; Ansari, Mujtaba; Pittman, Jon K. (Frontiers in Plant Science, 2022)
Sugar-Will-Eventually-be-Exported-Transporters (SWEETs) are an important family of sugar transporters that appear to be ubiquitous in all organisms. Recent research has determined the structure of SWEETs in higher plants, identified specific residues required for monosaccharide or disaccharide transport, and begun to understand the specific functions of individual plant SWEET proteins. However, in green algae (Chlorophyta) these transporters are poorly characterised. This study identified SWEET proteins from across representative Chlorophyta with the aim to characterise their phylogenetic relationships and perform protein structure modelling in order to inform functional prediction. The algal genomes analysed encoded between one and six SWEET proteins, which is much less than a typical higher plant. Phylogenetic analysis identified distinct clusters of over 70 SWEET protein sequences, taken from almost 30 algal genomes. These clusters remain separate from representative higher or non-vascular plant SWEETs, but are close to fungi SWEETs. Subcellular localisation predictions and analysis of conserved amino acid residues revealed variation between SWEET proteins of different clusters, suggesting different functionality. These findings also showed conservation of key residues at the substrate-binding site, indicating a similar mechanism of substrate selectivity and transport to previously characterised higher plant monosaccharide-transporting SWEET proteins. Future work is now required to confirm the predicted sugar transport specificity and determine the functional role of these algal SWEET proteins.